Gejala Ponteng Sekolah Antara Para Pelajar Sekolah Menengah - Mat Kilau, Idris (1997)
The purpose of this study was to investigate (a) the correlation between four independent variables and truancy among form four students and (b) to identify which of among the four independent variables influences the act of absenteeism in schools. Four aspects has been taken into account namely school factors, problems faced by the student, influences among peer group and environmental factors. This study was done on the form four students which had the highest record of absenteeism among sixteen secondary school in the Lower Perak District. The sample consisted of 720 students. A self-construcfed 40-items questionnaires were used for data collection to measure the variables. The data was collected through questionnaires and interviews. A pilot test was carried out to ensure the validity and reliability of the instrument (Cronbach’s Alfa = 0.7712). To analyse the correlation and regression of the data, Statistical Packages for Social Science (SPSS) version 7.5 were used. The finding of the study showed that students’ personal problems and environmental factors were the most dominant and influenced the act of truancy among the students in the Lower Perak district.